2023
DOI: 10.1186/s12929-022-00894-z
|View full text |Cite
|
Sign up to set email alerts
|

Intimate communications within the tumor microenvironment: stromal factors function as an orchestra

Abstract: Extensive studies of the tumor microenvironment (TME) in the last decade have reformed the view of cancer as a tumor cell-centric disease. The tumor microenvironment, especially termed the "seed and soil" theory, has emerged as the key determinant in cancer development and therapeutic resistance. The TME mainly consists of tumor cells, stromal cells such as fibroblasts, immune cells, and other noncellular components. Within the TME, intimate communications among these components largely determine the fate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…Previous studies [ 12 , 13 , 14 ] reported that the survival rate could be independently evaluated by the frequency of various tumor-infiltrating lymphocytes in patients bearing a solid malignant tumor as well as a hematologic tumor. We explored the underlying connection between the five candidate genes and their characteristic immune infiltration in a tumor-immune microenvironment via the TIMER and EPIC databases.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 12 , 13 , 14 ] reported that the survival rate could be independently evaluated by the frequency of various tumor-infiltrating lymphocytes in patients bearing a solid malignant tumor as well as a hematologic tumor. We explored the underlying connection between the five candidate genes and their characteristic immune infiltration in a tumor-immune microenvironment via the TIMER and EPIC databases.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a schematic is drawn to elucidate their recent medicines and therapy mechanisms in OS, as shown in Figure 3. Medicines used to inhibit and suppress tumorigenesis, metastasis, immune evasion, and chemoresistance via communication mediums [102]. Targeted therapies can be developed to intensify the therapies and achieve higher cure rates by having a thorough understanding of the roles of genes in communication axes and signalling pathways [103].…”
Section: Recent Osteosarcoma Therapiesmentioning
confidence: 99%
“…Associated with local or distant cells, tumor cells interact with the local or distant microenvironment, contributing to secondary malignant growth. Alterations in the tumor microenvironment play a vital role in the progression of malignant tumors, among which imbalance in the composition of immune cells, changes in the phenotype of fibroblasts and alterations in endothelial cells are characteristic of malignant lesions ( 19 21 ). Recently, there was an upward trend in the amount of studies, which have shown that never can people ignore the significance of exosomes to tumorigenesis, progression, associated immune responses, chemotherapy resistance and metastasis ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%